I can scrawl and I can crawl: drawing towards New Narrative. Issue 8 (3rd August 2021) - Merport Quiñones, Carmen
ABSTRACT: To get traction on the politics of form that we call 'New Narrative', I argue that we must defy disciplinary constraints and resist neglecting activities taking place away from the printed page. Looking closely at some of the visual work of Kathy Acker, this essay examines the radical ways in which the author brought drawing and writing together. It shows how the dream maps of Blood and Guts in High School foreclose familiar modes of literary consumption and call attention to the kinds of embodied encounters that take place when we can't rely on our usual modes of (graphic) self-abstraction. Such encounters, I suggest, represent a challenge for critics, insofar as they require us to develop concepts that allow us to join authors like Acker in gesturing toward the subjects, objects, and practices that exist in the spaces between artistic and academic disciplines.